RACISM AND MENTAL HEALTH AMONG BLACK WOMEN WORKERS IN BRAZIL’S UNIFIED HEALTH SYSTEM (SUS): AN INTEGRATIVE REVIEW (2019–2025) (CIPEEX, 2025)
Introduction: Gender- and race-based inequities permeate work processes in Brazil’s Unified Health System (SUS) and intensify psychological distress among Black women workers, who report harassment, weaker institutional support, and everyday barriers¹, ⁶. Objective: To examine whether Black women working in the SUS experience racism and whether this leads to greater mental ill-health. Methods: Integrative review (2019–2025) in PubMed and SciELO using the descriptors racism AND SUS workers AND work processes AND mental health. Inclusion: Brazilian studies with SUS (or public-sector) workers that analyzed race/skin color and mental-health outcomes—common mental disorders (CMDs), stress, burnout—or workplace racism; exclusion of editorials, letters, and duplicates. Results: The search retrieved 39 records; after removal and screening, 16 texts were eligible and 7 fully met criteria. The synthesis indicates an association between perceived racism and psychological distress in health-care work contexts³; intersectional gender–race–class effects in the distribution of CMDs²; and greater mental-health impact, harassment, and reduced access to resources among Black women during the pandemic⁴, ⁵, ⁶. Qualitative studies with Black women physicians describe emotional exhaustion, institutional racism, and career setbacks¹, ⁶, whereas surveys of health-service workers show that discrimination/harassment raises CMD prevalence⁷. Conclusions: Racism experienced by Black women in the SUS is associated with worse mental-health outcomes. We recommend embedding anti-racism in continuing education, workforce management, and occupational-health surveillance, with psychosocial support and routine monitoring by race/skin color¹, ⁷.